The Consensus of Different Fractional-Order Chaotic Multiagent Systems Using Adaptive Protocols - Masoumeh Firouzjahi; Bashir Naderi; Yousef Edrisi Tabriz (Journal of Mathematics)
This paper is concerned with the adaptive consensus problem of incommensurate chaotic fractional order multiagent systems. Firstly, we introduce fractional-order derivative in the sense of Caputo and the classical stability theorem of linear fractional order systems; also, algebraic graph theory and sufficient conditions are presented to ensure the consensus for fractional multiagent systems. Furthermore, adaptive protocols of each agent using local information are designed and a detailed analysis of the leader-following consensus is presented. Finally, some numerical simulation examples are also given to show the effectiveness of the proposed results.